Surviving Disasters: Salim's Journey through Hell (The Never-ending Saga of the Bhopal Gas Tragedy) - Mukherjee, Suroopa (New Delhi Teri Press, 2014)
Adventure takes place inside a defunct, killer factory in Old Bhopal, 24 years after the Bhopal Gas Tragedy took place. As Salim and his friends make their way through the ghost like remnants of the industrial disaster, time seems to stand still from that fateful night of 1984. What happens next is a saga of the renewed search for truth by the blighted children, born to the survivors of the Bhopal Gas Tragedy.
Keywords: English Fiction; Children book